Analisis Perilaku Perundungan (Bullying) di SDN Berangas Timur 1: Analysis of Bullying Behavior at SDN Berangas Timur 1 - Nur Khalifah Agustina; Ali Rachman; Eklys Cheseda Makaria (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Bullying behavior in elementary schools is a problem that affects and disrupts most learning environments in schools. Bullying behavior also hinders students' personal, social, and learning development, requiring action from the school and guidance and counseling services. This study aims to analyze and describe bullying behavior among fifth-grade students at SDN Berangas Timur 1, including its forms, the factors behind it, and its impacts. In addition, it aims to examine its relationship with Albert Bandura's social learning theory and guidance and counseling in elementary schools. This study uses a descriptive quantitative approach. The research subjects were 48 students in grades VA and VB at SDN Berangas Timur 1. The data collection technique used a bullying behavior questionnaire that has passed validity and reliability tests. Data were analyzed using descriptive statistics, presented as percentages and score categories. The study found that bullying behavior at SDN Berangas Timur 1 was relatively low, though it still occurred frequently. The dominant forms of bullying were physical, verbal, and relational bullying. The dominant influencing factor for bullying was personal factors (self-confidence), and the perceived impact encompassed all aspects (physical, psychological, academic, and social).